2003
DOI: 10.1093/toxsci/kfg188
|View full text |Cite
|
Sign up to set email alerts
|

Application of the CFU-GM Assay to Predict Acute Drug-Induced Neutropenia: An International Blind Trial to Validate a Prediction Model for the Maximum Tolerated Dose (MTD) of Myelosuppressive Xenobiotics

Abstract: In a previous study of prevalidation, a standard operating procedure (SOP) for two independent in vitro tests (human and mouse) had been developed, to evaluate the potential hematotoxicity of xenobiotics from their direct and the adverse effects on granulocyte-macrophages (CFU-GM). A predictive model to calculate the human maximum tolerated dose (MTD) was set up, by adjusting a mouse-derived MTD for the differential interspecies sensitivity. In this paper, we describe an international blind trial designed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 46 publications
2
97
2
3
Order By: Relevance
“…On the basis of these observations, it has been suggested that compounds with little differential in bone marrow sensitivity across species may have greater potential for reaching similar blood levels in patients as in mice (25). So, on the basis of the CFU-GM assay developed by Pessina and colleagues (46) and validated in several studies (26,47,48), we demonstrated that the mouse bone marrow is only about 5-fold less sensitive than human bone marrow, thus suggesting that EMICORON could reach a similar blood levels in humans as in mice. This is in line Real-time tumor dissemination was monitored by the imaging system.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these observations, it has been suggested that compounds with little differential in bone marrow sensitivity across species may have greater potential for reaching similar blood levels in patients as in mice (25). So, on the basis of the CFU-GM assay developed by Pessina and colleagues (46) and validated in several studies (26,47,48), we demonstrated that the mouse bone marrow is only about 5-fold less sensitive than human bone marrow, thus suggesting that EMICORON could reach a similar blood levels in humans as in mice. This is in line Real-time tumor dissemination was monitored by the imaging system.…”
Section: Discussionmentioning
confidence: 99%
“…Colony counts (normalized as a percentage of control) at each concentration were then plotted to generate the concentrationresponse curve. As previously reported (Erickson-Miller et al, 1997;Parchment et al, 1994Parchment et al, , 1998Pessina et al, 2003), the endpoint of the assay for quantifying inter-species differences in susceptibility to drug toxicity is the IC 90 , which is the concentration that inhibits colony formation by 90%. IC 90 values were calculated from log-linear regression on concentrationresponse between the flanking data points on either side of the 90% inhibition level.…”
Section: In Vitro Comparative Myelotoxicity Assaymentioning
confidence: 93%
“…Bone marrow is critically sensitive to nucleoside analogs (11). It is important to understand the toxicity of agents to bone marrow, and to determine whether bone marrow progenitor cells will have greater or less sensitivity to the agent than human malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow granulocytemacrophage-colony forming unit (CFU-GM) assays that compare the sensitivity of bone marrow cells across species are useful in predicting the blood levels of an agent that might be achieved in patients using blood levels tested in preclinical efficacy and safety studies as a guide. Mouse bone marrow is less sensitive to many cytotoxic agents than is human bone marrow, allowing blood levels in preclinical efficacy testing that can not be achieved in patients (11)(12)(13)(14)(15). An efficacious level of a compound with smaller or no differential in bone marrow progenitor sensitivity among species may have a better potential for reaching similar blood levels in patients as in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation